1999
DOI: 10.1080/00034989958005
|View full text |Cite
|
Sign up to set email alerts
|

Acute, hepatitis-A super-infection in HBV carriers, or chronic liver disease related to HBV or HCV

Abstract: The impact of acute super-infection with hepatitis A virus (HAV) was determined in 20 asymptomatic carriers of the surface antigen (HBsAg) of hepatitis B virus (HBV), eight patients with HBV-related chronic liver disease (CLD), and four patients with CLD related to hepatitis C virus (HCV). For comparison, 100 patients with isolated HAV infection were also studied. The HBsAg carriers and patients with CLD related to HBV or HCV were significantly older than the patients with isolated HAV infection, with mean (S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Although HAV transmission is rarely blood-borne and hemophilic patients are at no greater risk of this infection than the general population, in those already chronically infected with HBV and/or HCV, an additional acute HAV infection may have additional adverse effects on chronic liver disease (37). It is therefore reasonable to recommend routine HAV vaccinations for this population in particular.…”
Section: Discussionmentioning
confidence: 99%
“…Although HAV transmission is rarely blood-borne and hemophilic patients are at no greater risk of this infection than the general population, in those already chronically infected with HBV and/or HCV, an additional acute HAV infection may have additional adverse effects on chronic liver disease (37). It is therefore reasonable to recommend routine HAV vaccinations for this population in particular.…”
Section: Discussionmentioning
confidence: 99%
“…One-third of the patients were not tested for hepatitis A immunity, which could represent missed opportunities to provide vaccine protection, which could lead to serious clinical consequences. For example, one study found that 11 of 20 patients with acute hepatitis A and CHB developed fulminant or submassive liver necrosis, whereas 100 patients with acute hepatitis A and no underlying chronic liver disease recovered fully (17). Compared with infectious disease physicians, gastroenterologists were often remiss in their adherence to testing for HCV and HIV co-infection.…”
Section: Discussionmentioning
confidence: 99%
“…Vento et al reported that, among 10 patients with an acquired HAV superinfection and chronic HBV infection, one (10%), who had cirrhosis, had marked cholestasis [ 9 ]. Pramoolsinsap et al evaluated acute superinfection with HAV in 20 HBV asymptomatic carriers and fulminant hepatitis or submassive hepatitis in 11 (55%) of 20 HBsAg carriers [ 63 ]. A superinfection of HAV in patients with HBV occasionally leads to critical conditions in HBV carriers with or without cirrhosis, although patients with advanced fibrosis or cirrhosis are more susceptible to severe conditions [ 9 , 21 , 57 , 58 , 59 , 60 , 61 , 62 , 63 ].…”
Section: Coinfection Of Hav With Hbvmentioning
confidence: 99%